English words used in modern young people's speech - Usarova Nilufar Yakubovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Language and humanity are the same part of life as language is developed with humans. Language is changed as humans are changed. Language is like a living thing. Words are born in it, and live; some words go away and others stay forever. Each generation brings its own vocabulary. Some people find it positive, some negative. Philologists admit that there is nothing wrong with youth slang. Many teenagers use it until a certain age and then return to literary language.